The Development of the Terminology of Al-Hadith Al-Hassan Among the Speakers from Establishment to Stability - Mohamed , Ahmed (Islamic Sciences Journal, 2023)
There has been widespread among many students of this science in this time is a dispute between what they are called (the method of the previous ancestors or advanced) and (the method of the later ones) in the sciences of hadith. This dispute needs reviewing and checking in order to stop on its truth. Is this dispute on the face's truth or it it reflects various of view on its general terminology as they say ( everyone has no single response that is right and the other is wrong ) in order to make the result correct we have to approve that the origin in each science is the first who wrote in. Among these terms is ((Al-Hadith Al-Hassan), which was differently inferred by the ancients and the later ones. The researcher has a view to discuss it in a single research to show its birth and development as well as its significance for the ancestors(advanced) and later ones.